Decision Making Strategy Using the Assignment Method with the POM-QM Application - I Made Aryata; I Gede Marendra (PT FORMOSA CENDEKIA GLOBAL, 2022)
The assignment method is a model related to the network. The assignment method includes the process of delegating tasks or work to resources. The goal most often is to minimize the total cost or time required to carry out the task at hand. One of the most important characteristics of the assignment problem is that there is only one job assigned to a machine (or project). Problem solving using the assignment method has been taught in Operations Research courses where the calculation process is done manually. Therefore, POM-QM for Windows application training is provided to help solve assignment method problems quickly and precisely. From the results of the training given, the participants already knew how to use the POM-QM for Windows application and how to solve assignment method problems with the POM-QM for Windows application.